Exploring dynamics in larval fish diversity, assemblages, and abundance across four mangrove areas in Peninsular Malaysia - IZZATI ADILAH AZMIR; YUZINE ESA; M. AQMAL-NASER; INA SALWANY MD YASIN; S. M. NURUL AMIN; FARIDA ZURAINA MOHD YUSOF; AMIRRUDIN AHMAD (Society for Indonesian Biodiversity, 2025)
Abstract. Azmir IA, Esa Y, Aqmal-Naser M, Yasin ISM, Amin SMN, Yusof FZM, Ahmad A. 2025. Exploring dynamics in larval fish diversity, assemblages, and abundance across four mangrove areas in Peninsular Malaysia. Biodiversitas 26: 1229-1237. Understanding larval fish populations is crucial for assessing the impact of habitat disturbances and ensuring consistent stock recruitment. However, challenges include extensive sampling requirements, time-consuming identification, and limited identification keys. This study aims to explore larval fish diversity, assemblages, and abundance in four mangrove areas across Peninsular Malaysia: Matang (Perak), Pekan (Pahang), Setiu (Terengganu), and Pendas (Johor). Sampling was conducted during the highest tide and full moon phases using a Bongo net (500 ?m mesh size, 60 cm diameter) towed at 0.5 m depth, with a flow-meter to calculate the water volume filtered. Larval fish were identified to the nearest genus or species. Pendas exhibited the highest species diversity, richness, and evenness, whereas Setiu recorded the lowest. Species compositions varied across sites, with Gobiidae dominating in Pekan, Matang, and Pendas; Clupeidae in Pendas; and Engraulidae across all sites except Setiu. Community similarity was assessed, showing 20% similarity between Matang, Pekan, and Pendas, and 30% similarity between Matang and Pekan. All sites were dissimilar at a 40% similarity threshold. Pendas also hosted the highest number of unique species (n: 13), followed by Pekan (n: 6), Matang (n: 5), and Setiu (n: 3). Species overlap was noted, with Pendas sharing nine species with Pekan, five with Matang, and one with Setiu. These findings offer valuable insights for conservation efforts, emphasizing the importance of safeguarding larval fish populations and their habitats to support ecosystem health and fish recruitment. This study provides crucial data for decision-makers to implement targeted conservation strategies to preserve larval fish diversity and mitigate the effects of habitat disturbance.